3D image of Inoue balloon inflation during mitral valvuloplasty - Doubell, Anton F.; Swanevelder, J.; Weich, H.; Herbst, P. (SA Heart Journal, 2017)
Mitral balloon valvuloplasty is an important intervention in the armory of the cardiologist, offering a safe and effective percutaneous option in the treatment of patients with mitral stenosis.